Predicting daily lactation costs of marine mammals for use in bioenergetic models - Elizabeth A. McHuron (PLoS ONE, 2026)
Empirical estimates of energetic processes are limited or absent for many marine mammal species, hindering the ability to quantify disturbance-related impacts on population dynamics using bioenergetic approaches. In this study, published estimates of mass-specific milk intake rates and milk energy density from marine mammals and taxonomically related terrestrial mammals were used to examine how these variables changed as a function of the percentage of time into the lactation interval. Predictions of milk energy intake derived from these relationships were compared with independent estimates from other approaches to inform their utility in estimating daily lactation costs of data-poor species. Daily mass-specific milk intake rates declined between the start and end of lactation for all taxonomic groups, but the rate of decline was much steeper for ursids, artiodactyls, and mustelids than it was for otariids or phocids. Similarly, most taxonomic groups exhibited some increases in milk energy density as lactation progressed, but the magnitude and timing varied among families. Comparisons with independent estimates revealed the likely utility for using the derived relationships in estimating daily lactation costs of data-poor phocids, otariids, and mustelids, with some caveats. There was a large mismatch in the temporal pattern between independent estimates for cetaceans and predictions derived from semi-aquatic and terrestrial species, indicating that cetaceans have higher mass-specific milk intake rates early in lactation compared to most other species that then rapidly decline during the first 10–25% of the lactation interval. Such differences may be an adaptation to a fully aquatic lifestyle and highlight the importance of other methods for estimating daily lactation costs of data-poor cetaceans in bioenergetic models.